Do Social Influence and Rationalization Determine the Use of Artificial Intelligence-ChatGPT in Higher Education Learning? - Evamillatul Qistiyah; Muhammad Sabandi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The use of AI-ChatGPT in education is a compelling topic, although research is limited due to its recent rapid development, necessitating further studies. This quantitative study used descriptive statistical analysis and involved 190 active students using ChatGPT in Indonesian higher education students. Purposive sampling was used for data collection via an online questionnaire. The gathered data were processed through partial least square technique. Purposive sampling was used for data collection via an online questionnaire. Validity was tested with Convergent and Discriminant Validity, and reliability with Cronbach's Alpha and Composite Reliability. The finding reveal that ChatGPT Use influence by social influence, rationalization, perceived usefulness, and perceived ease of use. Similarly, social influence significantly influences on perceived usefulness and perceived ease of use. Rationalization also significantly influences on perceived usefulness and perceived ease of use. Social Influence and Rationalization increase ChatGPT use in learning, with perceived Usefulness mediating the relationship and perceived ease of use also mediating it.